Control of Presynaptic Parallel Fiber Efficacy by Activity-Dependent Regulation of the Number of Occupied Release Sites - Schmidt, Hartmut (Frontiers in Systems Neuroscience, 2019)
Parallel fiber (PF) synapses show pronounced and lasting facilitation during bursts of high-frequency activity. They typically connect to their target neurons via a single active zone (AZ), harboring few release sites (~2-8) with moderate initial vesicular release probability (~0.2-0.4). In light of these biophysical characteristics it seems surprising that PF synapses can sustain facilitation during high-frequency periods of tens of action potentials (APs). Recent findings suggest an increase in the number of occupied release sites due to ultra-rapid (~180 s-1), Ca2+ dependent recruitment of synaptic vesicles (SVs) from replenishment sites as major presynaptic mechanism of this lasting facilitation. On the molecular level, Synaptotagmin 7 or Munc13s have been suggested to be involved in mediating facilitation at PF synapses. The recruitment of SVs from replenishment sites appears to be reversible on a slower time-scale, thereby, explaining that PF synapses rapidly depress and ultimately become silent during low-frequency activity. Hence, PF synapses show high-frequency facilitation but low-frequency depression. This behavior is explained by regulation of the number of occupied release sites at the AZ by AP frequency.